Controlled Substance Agreements for Opioids in a Primary Care Practice - Lindsey M. Philpot; Priya Ramar; Muhamad Y. Elrashidi; Raphael Mwangi; Frederick North; Jon O. Ebbert (Taylor & Francis Group, 2017)
Background Opioids are widely prescribed for chronic non cancer pain (CNCP). Controlled substance agreements (CSAs) are intended to increase adherence and mitigate risk with opioid prescribing. We evaluated the﻿ demographic ﻿characteristics of a﻿nd opioid dosing for patients with CNCP enrolled in ﻿CSAs in a primary care practice. Methods We conducted a retrospect﻿ive cohort study of﻿ 1066 patients enrolled in CSAs between May 9, 2013﻿ and August 15, 2016 for CNCP in a Midwest primary care practice. Results Patients were prescribed an average of 40.8 (SD ± 57.0) morphine milligram equivalents per day (MME/day), and 21.5% of patients were receiving ≥50 MME/day and 9.7% were receiving ≥90 MME/day. Patients who were younger in age (≥ 65 vs. < 65 years, P < 0.0001), male gender (P = 0.0001), and used tobacco (P = 0.0002) received significantly higher MME/day. Patients with more co-morbidities (Charlson Comorbidity Index, CCI) received higher MME/day (CCI > 3 vs. CCI ≤ 3, P = 0.03), and reported higher average pain (CCI > 3 mean 5.8 [SD ± 2.1] vs. CCI ≤ 3 mean 5.3 [SD ± 2.0], P = 0.0011). Patients on an identified tapering plan (6.9%) had higher MME/day than patients not on a tapering plan (P = 0.0002). Conclusions CSAs present an opportunity to engage patients taking higher doses of opioids in discussions about opioid safety, appropriate dosing and tapering. CSAs could be leveraged to develop a population health management approach to the care of patients with CNCP.